Integrated Solar Energy Application System Development to Catalyze Public Participation Towards Bali Clean Energy Through Crowd-Based Business Models - Arifin, Sadiid; Firdaus S. A., Al Hilal; Putri, Azarine Raina Erwita (Indonesian Journal of Energy, 2022)
Through the Minister of ESDM K/20/MEM/2015 and Bali Governor Regulation No. 45/2019, Bali is designated as a clean energy area and has the advanced implementation of the energy transition towards renewable energy to attain SDG 7 "Affordable and Clean Energy." One of the main intensified directions is the development of solar rooftop energy. However, its development has encountered obstacles that hinder the operation's sustainability. Constraints include financing and community participation. This paper aims to provide solutions to catalyze public participation (especially in youth) for energy transition through the Crowd-Based Business Model, especially for Rooftop Solar Energy Power Plant or PLTS Atap. An integrated information system in the application that can increase investor interest in renewable energy, especially PLTS Atap, could be the answer. This Study uses data from literature studies and will be processed through qualitative content analysis, business model canvas, system design/flow analysis and SWOT analysis. This research will produce an application that is expected to be able to (1) understand the potential, benefits and considerations in using renewable energy, especially solar energy, by installing PLTS Atap in Indonesia (2) inform about financing schemes for installing and using PLTS Atap as a source of electricity generation on a corporate industrial and commercial scale (3) explain investment alternatives using crowdfunding and crowd sale with a certain level of profit that supports environmental values and renewable energy.